Public–private partnerships as gateway to sustainable development in Bosnia and Herzegovina - Omercic Jasmin, OJ (Islamic Finance News, 2022)
Apart from the undeniable potential of the ‘nearshoring’ strategy of Bosna Bank International (BBI) to harness socioeconomic growth in Bosnia and Herzegovina (B&H) after the COVID-19 pandemic, public–private partnerships (PPPs) represent another gateway to attaining the SDGs in B&H. It is doubtlessly not the first time that PPPs are at the center of discourse in B&H but it surely is an unexplored arena that can become the next ‘Loi de l'Attraction’ (Law of Attraction) to angel investors, traders, merchants or manufacturers in the heart-shaped Balkans nation.